THE RELATIONSHIP BETWEEN PARENTING STYLES AND CHILDREN'S SELF-CONFIDENCE IN THE KUTA ALAM WORKING AREA BANDA ACEH CITY - Ritawati Ritawati; Nurhayati Nurhayati; Eka Warnidar (Getsempena Health Science Journal, 2024)
The role of parents is crucial in shaping several fundamental attitudes that determine the development of a child’s personality in the future. Having self-confidence is very important for the growth and development of a child's personality. Applying appropriate and correct parenting styles is a way for parents to help develop their children's self-confidence. The aim of this study is to determine the relationship between parenting styles and children's self-confidence in Kuta Alam Working Area, Banda Aceh City. This research uses a descriptive analytic design with a cross-sectional approach. The sampling technique used is total sampling, involving the entire population as the sample. The study includes all mothers who have children aged 6–10 years in Kuta Alam Working Area, Banda Aceh City, totaling 65 respondents. The research instrument used is a questionnaire sheet. Data analysis was carried out univariately and bivariately using the chi-square test. The results showed that the majority of respondents applied a permissive parenting style, with 33 respondents (50%), and most children had low self-confidence, with 26 respondents (39.4%), while a small portion had moderate self-confidence, with 17 respondents (25.8%). There is a significant relationship between parenting style and children's self-confidence, with a p-value of 0.002 (p<0.05). It is recommended that parents adopt effective parenting styles, especially those oriented toward democratic parenting, and support every stage of child development so that children can enhance their self-confidence and social abilities.